Pelatihan Pembuatan Pupuk Kompos Melalui Pemanfaatan Limbah Rumah Tangga Di Lingkungan Bagik Longgek Kecamatan Selong Kabupaten Lombok Timur - Ariandani, Nunung; Ermanda, Sandy; Fatmawati, Baiq (Universitas Hamzanwadi, 2022)
The strategic potential of the West Bagik Longgek Environment with the potential of natural resources, especially agriculture, is an economic attraction to increase people's income. So far, people are not used to utilizing household waste and the potential of surrounding resources to produce products that have more economic value. This Community Service Program aims to provide insight into finding creative ideas for processing household waste, especially natural fertilizer. The method used in this service activity is carried out in 4 stages: observation, preparation, implementation, monitoring, and evaluation. Compost fertilizer from household waste in the form of rice washing water, stale rice and vegetable residues, and or fruit skins, and EM4 fertilizer is added as a catalyst in making compost. Household waste that has no economic value will have a proper value when it can be reprocessed into something useful, one of which is compost. The compost produced from this activity is dark brown to black, similar to the color of the soil, insoluble in water, and odorless, so it can be concluded that the quality of the compost produced is quite good